Bidai dan Takin Dalam Perspektif Sosio-Ekonomi Masyarakat Perbatasan Indonesia-Malaysia - Budiman, Jumardi (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2018)
The context of this research was on the phenomenon of economy and socio culture mobilities on Dayaknese society in Seluas and Jagoi Babang district which are Indonesia – Malaysia borderland. The economy and social mobilities occured on the trade of plaited handicraft Bidai and Takin which are the culture heritage of Dayaknese society in Indonesia-Malaysia borderland. The approach used in this research was qualitative approach by data validity test such as credibility, dependability, and confirmability tests. Source of data and the informen as well in this research were the craftsmen and distributors of Bidai and Takin. The resesarch finding showed there was the economy mobilities such as the plaited handicraft products trading and the social mobilities such as the claim of the culture heritage rights by the distributor from Malaysia.Keywords: bidai and takin, socio-economy, borderland people